Rating of Perceived Exertion and Affective Responses during Tai Chi Chuan. Issue 3 (June 2014) - Chao, Cheng H. N.; Costa, Eduardo C.; Okano, Alexandre H.; Farias, Thiago de Brito; Farias, Luiz Fernando; Elsangedy, Hassan M.; Krinski, Kleverton
Ratings of perceived exertion (RPE) and affective responses were assessed during Tai Chi Chuan. A total of 16 women ( M age = 61.2 yr., SD = 8.8) participated in this study. Individuals practiced Tai Chi Chuan three times / week during seven weeks, and were assessed session-by-session (21 Wu Tai Chi Chuan sessions) in three moments (15, 30, and 45 min.) using Borg's scale (CR 0–10) and the Feeling Scale (+5/–5). With regard to RPE, there was a difference between 15 and 30 min. and between 15 and 45 min. The same pattern of differences was observed for the affective response. The RPE during the seven weeks ranged from "fairly light" to "moderate" and the affective response from "good" to "very good." Thus, Tai Chi Chuan was perceived as a low-moderate intensity and pleasurable (positive affect) exercise by middle-aged and elderly women.